Novel dehydrins lacking complete K-segments in Pinaceae. The exception rather than the rule - Perdiguero, Pedro; Collada, Carmen; Soto, Álvaro (Frontiers in Plant Science, 2014)
Dehydrins are thought to play an essential role in the plant response, acclimation and tolerance to different abiotic stresses, such as cold and drought. These proteins contain conserved and repeated segments in their amino acid sequence, used for their classification. Thus, dehydrins from angiosperms present different repetitions of the segments Y, S and K, while gymnosperm dehydrins show A, E, S and K segments. The only fragment present in all the dehydrins described to date is the K-segment. Different works suggest the K-segment is involved in key protective functions during dehydration stress, mainly stabilizing membranes. In this work, we describe for the first time two Pinus pinaster proteins with truncated K-segments and a third one completely lacking K-segments, but whose sequence homology leads us to consider them still as dehydrins. qRT-PCR expression analysis show a significant induction of these dehydrins during a severe and prolonged drought stress. By in silico analysis we confirmed the presence of these dehydrins in other Pinaceae species, breaking the convention regarding the compulsory presence of K-segments in these proteins. The way of action of these unusual dehydrins remains unrevealed.